Enhancing SIM behaviour in a mononuclear tetrahedral [Co(N,N′-2-iminopyrrolyl)2] complex - Ferreira, Patricia S.; Malta, Jose F.; Bandeira, Nuno A. G.; Allgaier, Alexander; van Slageren, Joris; Paixao, Jose A.; Almeida, Manuel; Pereira, Laura C. J.; Gomes, Pedro T. (Chemical communications (Cambridge, England), 2022)
A new homoleptic Co(ii) complex bearing two highly sterically congested 2-formiminopyrrolyl N,N '-chelating ligands is reported, displaying slow relaxation of the magnetisation at zero static (DC) field. This compound shows a large value for the zero-field splitting (ZFS) parameter D of -42.6(4) cm(-1) leading to a spin-reversal energy barrier U-eff of 85 cm(-1).